Ambient air pollution does not diminish the beneficial effects of active commuting on heart failure: a prospective study in UK Biobank - Qian Sun; Chaojun Yang; Min Jiang; Mudan Yang; Menglu Mao; Zhixing Fan (BMC Public Health)
Abstract Background Evidence on active commuting and heart failure (HF) under levels of air pollution exposure is limited, and little is known on the potential mediation roles of inflammation. The objective of this study was to investigate the association between active commuting and HF, as well as to ascertain whether air pollution may influence this relationship. Methods This prospective study included 241,786 participants without HF at baseline in UK Biobank. The commuting mode was recorded using questionnaire. We examined long-term exposure to air pollution, including particulate matter with an aerodynamic diameter smaller than 2.5 μm (PM2.5) or 10 μm (PM10), PM2.5–10, nitrogen dioxide (NO2), and nitrogen oxide (NOx). The incident HF was identified through linkages with medical records. Cox proportional hazard models were used to estimate the association of active commuting on HF under different air pollution concentrations. Furthermore, mediation analysis was performed to test the mediated role of inflammation. Results A median follow-up period of 13.7 years yielded 4485 incident cases of HF. Compared with non-active commuting, both cycling (HR = 0.66, 95%CI: 0.57–0.76) and walking mode (HR = 0.86, 95%CI: 0.78–0.94) were found to be associated with the reduced risk of HF, following the full adjustment for covariates, including PM2.5. The beneficial effect of cycling (HR = 0.68, 95%CI: 0.56–0.81) and walking mode (HR = 0.82, 95%CI: 0.72–0.92) on HF was also observed in the context of high PM2.5 exposure. The inflammatory response was responsible for mediating 21.97% and 13.83% of the effect of the association between cycling mode and walking mode and HF. Conclusions For those residing in regions with relatively elevated air pollution levels, active commuting may still be a viable strategy for the prevention of HF.